Gender differences in teacher-student interactions, attitudes and achievement in middle school science - Eccles, Lynette (Curtin University, 2006)
Research has shown that interest in science often decreases in the middle-school grades for both boys and girls, but that more boys continue on the science track in high school and college, leading to males dominating the fields of science and engineering in the work place. The interpersonal interaction between teachers and students, as both individuals and as a group, comprises a large part of the classroom learning environment. Though these interactions last only a school year, they can influence student attitudes and achievement in the long term. Past research has suggested that a key factor in improving student achievement and attitudes is to create learning environments which emphasize characteristics that have been found to be linked empirically with achievement and attitudes. The purpose of this study was to use quantitative methods to validate a learning environment questionnaire (Questionnaire on Teacher Interaction, QTI), to investigate outcome-environment associations, and to compare male and female students in terms of their attitudes, classroom environment perceptions and achievement. An attitude scale, based on items from the Test of Science Related Attitudes (TOSRA), and a 48-item eight-scale version of the QTI were administered to 1228 science students in Grades 6, 7 and 8 at one middle school in South Florida. Student achievement was measured using the students’ quarterly (nine-week) science grade.The results revealed satisfactory internal consistency reliability for the QTI, with alpha reliability coefficients ranging from 0.51 to 0.83 for different scales with the student as the unit of analysis and from 0.54 to 0.96 for class means. For the 10-item attitude scale, the alpha coefficient was above 0.80 for both the student and the class mean as the unit of analysis, demonstrating high internal consistency reliability. Overall, the results of the statistical analyses supported that the QTI questionnaire and the attitude scale are valid and reliable instruments for use with secondary science students in South Florida. A strong relationship was found between student outcomes (attitudes and achievement) and many of the eight QTI scales with either the individual or the class mean as the unit of analysis. For example, students’ attitudes towards science were more positive when teachers exhibited more leadership and understanding behaviors and science achievement was higher when teachers were friendlier and less uncertain. The use of MANOVA tentatively revealed gender differences in students’ perceptions of teacher interpersonal behavior, attitudes towards science, and science achievement. However, the differences between males and females were statistically significant only for the Helping/Friendly, Dissatisfied, and Admonishing scales of the QTI and for achievement. In general, relative to males, female students had more positive perceptions of teacher interpersonal behavior and higher academic achievement.